Energy Consumption Patterns in Transplanted Paddy Cultivation in India - De, Dipankar; Babu, V Bhushana (Journal of Agricultural Engineering, 2004)
Paddy is grown in 22.8 % of total cropped area of India. About 55 % of the area is under rainfed cultivation. Transplanted paddy cultivation is a better option than direct sown in terms of crop management and productivity. Energy use analyses were conducted on transplanted paddy cultivation (irrigated and rainfed) in 4839 audited farms of selected villages in 7 states between 1996 and 2001 under the All India Co-ordinated Research Project on ’Energy Requirement in Agricultural Sector’. Irrigated farms consumed 57 to 201 % more energy mainly through electricity, fertiliser and diesel than in rainfed farms and had 20.4 to 67.3 % higher crop productivity. Operational energy use was 40 to 50 % of the total energy usage. Irrigation was the most energy consuming operation in irrigated farms followed by tillage, harvesting, threshing and transplanting. Canal water irrigated farms used about 26 to 37 % higher irrigation energy and also had tendency of using higher tillage energy. In rainfed farms, tillage was the most energy consuming operation followed by threshing and harvesting operations. Rainfed farms used 15 % more energy in tillage and 35 % more energy in transplanting. In high yielding irrigated areas, tractor farms had highest energy productivity (0.196 kg/MJ) while in medium yielding irrigated areas animal + power tiller farms had highest energy productivity (0.306 kg/MJ). In rainfed areas, animal + tractor farms had highest energy productivity (0.371 kg/MJ). Overall energy productivity was highest (0.25 kg/MJ) in rainfed farms while for irrigated farms it was lower by 23.4 - 44.5 % exhibiting existence of law of diminishing return.